Program Potensi Desa dan Program Kesehatan Desa Salamrejo Kapanewon Sentolo Kabupaten Kulon Progo - Pawana, Sekhar Chandra (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
In the first semester of the 2021/2022 academic year, Atma Jaya Yogyakarta University carried out the 80th KKN under the name “KKN Society 5.0” and was held online. The KKN 103 Unit U group was placed in Salamrejo Village, Sentolo District, Kulon Progo Regency. Salamrejo Village is famous for its village potential, namely handicrafts made from agel leaf fiber. However, the marketing if this agel leaf fiber craft product has not yet been marketed directly to consumers digitally. Based on this problem, the KKN 103 group created a village potential work program, namely the marketing of agel fiber craft products digitally through e-commerce, the goal is to expand the marketing of agel leaf fiber craft products so that they can increase the income of the people in Salamrejo Village. The Pocket Book work program with the title Guidebook to improve Body’s Immune System during the Pandemic is carried out with the hope that the people of Salamrejo Village can better understand the application of good and correct health protocols and also know how to improve the immune system so as to avoid the spread of the Covid-19 virus. The Village Potential and Pocket Book work program is carried out using the literature study method. The output of the program is an interactive e-book and video that is delivered with a descriptive technique. It is hoped that the delivery of information will be easier to understand and useful for the people of Salamrejo Village.